Secukinumab Associated Choroidal Neovascularization - Edward B Miller; Oren S Yovel (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2022)
A previously healthy 38-year-old woman with non-radiographic spondyloarthritis (nrSpA) developed juxta-foveal Choroidal Neovascularization (CNV) in the right eye three months after starting treatment with the anti-IL-17A inhibitor secukinumab. As there was no sign of ocular inflammation, no known association with CNV and this rheumatic disease, and other etiologic etiologies were excluded, this biologic agent was the suspected cause. Drug discontinuation and treatment with bevacizumab resulted in full suppression of the neovascular activity. IL-17 has a purported etiologic role in ocular neovascular diseases. The onset of this process in a patient receiving anti-IL-17 therapy suggests a possible causative role requiring further clarification.